2014
DOI: 10.1088/0031-9155/59/14/3789
|View full text |Cite
|
Sign up to set email alerts
|

Optical dosimetry of radiotherapy beams using Cherenkov radiation: the relationship between light emission and dose

Abstract: Recent studies have proposed that light emitted by the Cherenkov effect may be used for a number of radiation therapy dosimetry applications. There is a correlation between the captured light and expected dose under certain conditions, yet discrepancies have also been observed and a complete examination of the theoretical differences has not been done. In this study, a fundamental comparison between the Cherenkov emission and absorbed dose was explored for x-ray photons, electrons, and protons using both a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 45 publications
8
159
3
Order By: Relevance
“…The Cherenkov spectrum plotted in the graph shown in (h) was generated using geant4-based simulations of a 6 MV x-ray beam irradiating a light-skinned tissue volume. 21 The QE curves were plotted from data supplied by the camera manufacturer.…”
Section: F 2 Processed Cherenkov Images Collected Using the Cmos mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cherenkov spectrum plotted in the graph shown in (h) was generated using geant4-based simulations of a 6 MV x-ray beam irradiating a light-skinned tissue volume. 21 The QE curves were plotted from data supplied by the camera manufacturer.…”
Section: F 2 Processed Cherenkov Images Collected Using the Cmos mentioning
confidence: 99%
“…18 In addition to quality assurance, 19 Cherenkov imaging is being examined for in vivo surface dosimetry and beam tracking for real-time treatment verification. 20,21 As a passive monitoring modality, Cherenkov imaging would neither require any further dose to the patient nor interfere with typical treatment protocols. Initial studies on the applications of Cherenkov imaging have shown feasibility of imaging repeatedly, and studies of the potential medical value are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The dose distribution is largely dictated by energetic electrons above the threshold value for Cherenkov emission. Indeed this is well known, as Monte Carlo simulations of dose often do not track secondary photons <200 keV because they contribute so little to the overall dose [4]. A Dose/Cherenkov comparison has been systematically examined in water, using the geometry of Figure 3, and showing measured data from depth dose and profile curves in Figure 4.…”
Section: Water Tank Imagingmentioning
confidence: 99%
“…The emission is dominant in the blue range (Fig 1(b)) and falls off significantly with increasing wavelength, yet most of the light emitted from tissue is highly attenuated in the UV-blue-green, due to hemoglobin absorption, and so most of the detected light is above 600 nm when imaging tissue. The intensity of emission is a strong function of particle energy (Fig 1(c)) [4], however, it is relatively constant in the megavoltage energy range used in radiation therapy. Attenuation within tissue is due to scattering as well as high absorption in the UV-blue-green wavelengths, and so the detected Cherenkov light from animals originates from superficial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] It was concluded that the Cherenkov emission is suitable for surface dosimetry applications. 7 In the present paper, we suggest the use of Cherenkov radiation produced by relativistic electrons for investigation of optical properties of human tissues. Since the features of Cherenkov radiation are well known, use of the Cherenkov radiation as a source of visible photons for the investigation of human tissue has several advantages:…”
Section: Introductionmentioning
confidence: 99%